Meckel Gruber syndrome: occurrence in non-consanguineous marriages - de Silva, M.V.; Senanayake, H.; Siriwardana, K.D. (My University, 2004)
Meckel Gruber syndrome is an uncommon, lethal, autosomal recessive disorder, associated consistently with polycystic kidneys, posterior encephalocoele and polydactly. We report three cases in non-consanguineous marriages, suggesting that the single gene defect occurs more commonly in non-consanguineous marriages than mutant genes associated with other autosomal recessive disorders that are usually related with consanguineous marriages. The usefulness of prenatal diagnosis is discussed.